Fractalkine receptor polymorphisms V249I and T280M as genetic risk factors for restenosis - Niessner, Alexander; Marculescu, Rodrig; Kvakan, Heda; Haschemi, Arvand; Endler, Georg; Weyand, Cornelia M.; Maurer, Gerald; Mannhalter, Christine; Wojta, Johann; Wagner, Oswald; Huber, Kurt (Thrombosis and Haemostasis, 2005)
The chemokine fractalkine (FKN) recruits leukocytes into lesions of the arterial wall, which may lead to restenosis after stenting. FKN also regulates proliferation of smooth muscle cells, another mechanism pivotal to neointimal thickening. We assessed the hypothesis that functionally important polymorphisms of the FKN receptor CX3CR1 influence restenosis after coronary stenting. Three hundred and sixty-five patients undergoing coronary stenting were genotyped for the CX3CR1 polymorphisms V249I and T280M. Restenosis occurred in 25% of patients, and recurrent (> 1) restenosis at the target lesion in 8%.The allele I249 was associated with an increased risk of restenosis (adjusted odds ratio 2.4, 95% confidence interval: 1.3–4.2,P = 0.003) and recurrent restenosis (odds ratio 2.7,95% confidence interval:1.3–5.9,P = 0.011).Particularly, patients with I249 lacking the allele M280 were at an elevated risk of restenosis (P = 0.006) and, accordingly, the haplotype containing I249 but not M280 was more frequent in patients with restenosis (P = 0.001). In conclusion, the CX3CR1 I249 allele is associated with an increased risk of restenosis while the CX3CR1 M280 allele might counteract the harmful influence of I249.These findings show the importance of the chemokine FKN and genetic variations of its receptor for restenosis after coronary stenting. Recognition of these inherited risk modifiers may help to individualize treatment of coronary stenosis.
Keywords: Restenosis; stent; chemotaxis; fractalkine; single nucleotide; polymorphism